ZAHIRIDDIN MUHAMMAD BABUR’S CREATIVE AND CONSTRUCTIVE ACTIVITIES - Mamazoxidova Gulsanam Khayrullo qizi (Scholars Digest Publishing, 2026)
This work highlights the creative activity of Zahiriddin Muhammad Babur. The study analyzes his contribution to urban planning, the construction of parks and buildings, and the development of cultural life. Babur's historical place as a creative ruler is substantiated.
Keywords: Sharq uygʻonish davri, Amir Temur, Umarshaikh Mirza, Kutlug Nigorkhanim, Andijan, Akhsi, Samarkand, Fergana, Kabul, India, Afghanistan, Babur's Garden, Agra, Shah Jahan, Taj Mahal, Babur's Book, Akbar.